EFFECTS OF RESISTANCE EXERCISE ON BLOOD PRESSURE IN HYPERTENSIVE PATIENTS OF CENTRAL INDIA: A PROSPECTIVE STUDY - AGARWAL, SONIKA; JAIN, MANILA; ARORA, SUMIT; SHEIKHER, CHANDER (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of this research were to see whether practicing resistance exercises alone can help to reduce the hypertension and can be considered as an adjunct to treat the hypertension. Methods: It is a prospective, cross-sectional, and descriptive study conducted in the Department of Physiology, Malwanchal University over a period of 3 years. This study was carried out with a sample of 60 participants who were explained the procedure of experiment and informed consent was taken from all the participants included in the study. Results: Systolic blood pressure, diastolic blood pressure, pulse pressure, and pulse rate were observed. Pre-test of resistance exercise group mean pulse rate is 79.52±4.14 beats/min (Mean±SD) reduced to 76.36±4.01 in post-test. Resistance exercise mean systolic blood pressure of pre-test 137.34±6.36 mmHg (Mean±SD) is reduced to post-test 134.65±6.35mm of Hg (Mean±SD). Pre-test of resistance exercise mean diastolic blood pressure 91.52±4.45 mmHg (Mean±SD) is reduced to post-test 88.45±4.31 mm of Hg. Conclusion: Resistance exercise alone lowers systolic and diastolic blood pressure in prehypertensive and stage-1 hypertensive patients. Hence, resistance training is advised as a technique for managing the systemic hypertension.